SEA CUCUMBER AS ANTICANCER AGENTS AND ITS DEVELOPMENT FOR FUNCTIONAL FOOD PRODUCTS - Ridhowati, Sherly; Zakaria, Fransiska Rungkat; Syah, Dahrul; Chasanah, Ekowati (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2014)
Indonesia is popularly known as sea cucumber (teripang) exporter in the form of dried teripang. Commonly known as beche-de-mer or gamat, sea cucumber has long been used as medicine and food by Asian and Middle East people. Recent study has shown that sea cucumbers contain active compounds that show potential health benefits and other biological properties such as antibacterial and antifungal products, anticoagulants, antihypertensives, immuno modulation, inhibitor of osteoclastogenesis. It was reported that sea cucumber posses aphrodisiacs, potentially improve immunity, anticancer and anticoagulation. Sea cucumber is also rich in collagen as a component of connective tissue which can further be converted into smaller molecule and act as bioactive substances. This review presents the potential of sea cucumber as a functional food especially to prevent cancer and strategy to develop sea cucumber-based functional food by enzymatic hydrolysis and in vivo study.